High Park Fire overview: burn severity - Nelson, Peter A., cartographer; Brogan, Daniel J., cartographer (Colorado State University. Libraries, 2015)
Provides an overview of the High Park Fire area; detailing burn severity and focusing on Skin Gulch and Hill Gulch.
Keywords: flood; survey; topography; wildfire; geomorphology; precipitation; erosion